2022
DOI: 10.1136/bmjopen-2022-068165
|View full text |Cite
|
Sign up to set email alerts
|

Representativeness in population-based studies of older adults: five waves of cross-sectional examinations in the Gothenburg H70 Birth Cohort Study

Abstract: ObjectivesTo describe representativeness in the Gothenburg H70 1930 Birth Cohort Study.DesignRepeated cross-sectional examinations of a population-based study.SettingGothenburg, Sweden.ParticipantsAll residents of Gothenburg, Sweden, born on specific birth dates in 1930 were invited to a comprehensive health examination at ages 70, 75, 79, 85 and 88. The number of participants at each examination was 524 at age 70, 767 at age 75, 580 at age 79, 416 at age 85, and 258 at age 88.Primary outcome measuresWe compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…One previous study investigating representativeness among 70-year-olds born 1930 in the H70 studies showed that participants had higher income, less neuropsychiatric and cerebrovascular diseases than same-aged individuals in Gothenburg. 44 However, education level and the proportion of individuals born in Sweden did not differ. 44 In addition, when comparing characteristics between the MRI sample and those who did not participate in the MRI examination, those who participated had higher education levels, higher scores on MMSE, and less often dementia.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…One previous study investigating representativeness among 70-year-olds born 1930 in the H70 studies showed that participants had higher income, less neuropsychiatric and cerebrovascular diseases than same-aged individuals in Gothenburg. 44 However, education level and the proportion of individuals born in Sweden did not differ. 44 In addition, when comparing characteristics between the MRI sample and those who did not participate in the MRI examination, those who participated had higher education levels, higher scores on MMSE, and less often dementia.…”
Section: Discussionmentioning
confidence: 89%
“… 44 However, education level and the proportion of individuals born in Sweden did not differ. 44 In addition, when comparing characteristics between the MRI sample and those who did not participate in the MRI examination, those who participated had higher education levels, higher scores on MMSE, and less often dementia. 31 There were no differences regarding the proportion of women 31 or individuals born in Sweden.…”
Section: Discussionmentioning
confidence: 89%
“…This is a comprehensive population study examining birth cohorts of older people in Gothenburg 13 . This study comprised one cohort born in 1944 (examined in 2014–2016 with a response rate of 72%; n = 1203) 13,14 …”
Section: Methodsmentioning
confidence: 99%
“…13 This study comprised one cohort born in 1944 (examined in 2014-2016 with a response rate of 72%; n = 1203). 13,14 The participants were interviewed face to face, providing information on different topics: comorbidity, lifestyle behaviours, nutrition, functional performance, medications, cohabitation and education level. From the total of 1203 persons, we included 791 who had MRI images available, and from them, 251 individuals did not have good visualization of either the tongue or the masseter.…”
Section: Design and Samplingmentioning
confidence: 99%
“…(2) Sampling in a cohort study or: the issue of representativeness Compared to the general socio-demographic composition of Switzerland, the SHeS-pilot study showed a tendency towards higher participation of better educated and high-income citizens, an issue typical for health cohorts (50,51) that leads to lower diversity regarding socio-economic status, migration experience or ethnic origin. Also, long-lasting cohort studies face the challenge of attrition bias in that the characteristics of those leaving the study differ from those remaining in the study (52).…”
mentioning
confidence: 99%